Convenient Preparation and Full Characterization of a Synthetically Useful Salt of the Dithianitronium Cation, SNSSbF6, from Readily Available Starting Materials - Cameron, T. Stanley; Mailman, Aaron; Passmore, Jack; Shuvaev, Konstantin V (Inorganic chemistry, 2005)
The synthetically useful SNSSbF6 is prepared, in good yield, from the reactions of S3N2Cl2 or S3N3Cl3 with stoichiometric amounts of AgSbF6 and S8 in liquid SO2. SNSSbF6 crystallizes monoclinic in space group C2/m (a = 9.740(2) Å, b = 6.644(2) Å, c = 5.334(1) Å, β = 90.58(2)°, Z = 2). The crystal structure was determined by standard methods and refined to R 1 = 0.019 and wR 2 = 0.048. The structure consists of discrete linear centrosymmetric SNS+ cations [S−N = 1.4871(10) Å] and almost octahedral SbF6 - anions, with weak cation−anion interactions. The lattice energy of SNSSbF6 was determined from the volume-based method as 525 ± 32 KJ mol-1 and the heat of formation of SNSSbF6(s) has been estimated as −1566 ± 24 KJ mol-1. The FT-IR, Raman, and 14N NMR spectra are reported, as well as an in situ study of the reaction of S3N2Cl2 with AsF5 in SO2 solution.